North Atlantic Regional Water Resources Study. Appendix M. Outdoor Recreation. - BUREAU OF OUTDOOR RECREATION WASHINGTON D C (1972)
The North Atlantic Regional Water Resources Study (NAR) will identify the problems involved in meeting the present and future needs of people. It will indicate the magnitude of these needs, and establish priorities for development to meet them. More precisely, the objectives of this framework study are.'The determinations in broad terms of overall basin requirements for water and related land resource development for municipal, industrial, and agricultural water supply; water quality, flood control, and drainage; hydroelectric power; navigation; watershed protection and management; outdoor recreation; fish and wildlife conservation; together with an appraisal of the capability of on-going programs of resource development to meet indicated present and prospective needs. The study involves also the formulation in general terms of a plan of development, including the indication of elements which would be required in the near future and the need for the priority of more detailed studies of tributary basin areas.' Appendix M to report dated Jun 72, AD-A036 616. See also Appendix N, AD-A036 634.